2010
DOI: 10.1542/peds.2009-2391
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Symptoms, Dietary Patterns, and Growth in Young Children With Autism Spectrum Disorders

Abstract: ASD children showed feeding symptoms from infancy and had a less varied diet from 15 months, but energy intake and growth were not impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
183
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(206 citation statements)
references
References 15 publications
16
183
4
3
Order By: Relevance
“…They may be nutritionally vulnerable with more extreme eating behaviors. 48,50,61,62 Treatment therefore is best managed by specialists and includes hunger inducement coupled with nutritional supplementation and sensory integration approaches (eg, tactile exposure on skin, and then oral motor desensitization, and shaping and fading). 42, 63 In cases of hyposensitivity, strongly flavored foods and beverages may be better accepted and worth trying.…”
Section: Management Of Selectivitymentioning
confidence: 99%
“…They may be nutritionally vulnerable with more extreme eating behaviors. 48,50,61,62 Treatment therefore is best managed by specialists and includes hunger inducement coupled with nutritional supplementation and sensory integration approaches (eg, tactile exposure on skin, and then oral motor desensitization, and shaping and fading). 42, 63 In cases of hyposensitivity, strongly flavored foods and beverages may be better accepted and worth trying.…”
Section: Management Of Selectivitymentioning
confidence: 99%
“…There are reports of food selectivity presented by these individuals, like consume of a limited range of food items, resistance to try different foods and behavioral problems at mealtime (5). Thus, impaired nutritional status is not unusual in patients with ASD (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies by Loonum and Veldemann (2013) as also by Oie (2014) informed that diet interventions like glutamine or casein free are common practices amongst parents of children with autism. Above findings showed that dietary treatments is used to influence on child's development and behaviour, which is a common finding in Western research (Emond et al 2010;Whiteley et al 2010). …”
Section: Medical Researchmentioning
confidence: 67%